Accountability and responsibility in health care issues in addressing an emerging global challenge - Rosen, Bruce.; Israeli, Avi.; Shortell, Stephen M. 1944- (World Scientific series in global healthcare economics and public policy, 2012)
Serious scholarly analyses of the types and roles of accountability in health care first appeared in the late 1980s. That issue, along with the related issue of responsibility in health care, has continued to interest policymakers, analysts and scholars ever since. Indeed, there has been a renewed surge of interest in recent years, with growing attention to the notion of accountable care organizations in the US, clinical audits in the UK, and governance as stewardship in many other countries. Accountability and responsibility in health care was also the theme of a major international conference organized by the Israel National Institute for Health Policy Research, which was held in Jerusalem in 2009. This book is a collection of scholarly articles on the themes of accountability and responsibility in health care and seeks to be the premier book in that field. It includes selected papers from the 2009 Jerusalem Conference, analytic essays on how accountability and responsibility are playing out in eight different countries, and reprints of some of the classic articles in the field. The book will interest policymakers, managers, researchers and students, and many of the ideas presented here will help shape the development of this field in the years ahead. Some of these ideas have appeared in other forums; the unique contribution of this volume is that it is the first to bring together so many different perspectives on accountability and responsibility in health care. This volume will both acquaint readers with some of the latest thinking on accountability and responsibility in health care, and will serve as a catalyst for future reflection, research and writing in this area.